Whole-Exome Sequencing in 22 Young Ischemic Stroke Patients With Familial Clustering of Stroke. Issue 4 (April 2020) - Ilinca, Andreea; Martinez-Majander, Nicolas; Samuelsson, Sofie; Piccinelli, Paul; Truvé, Katarina; Cole, John; Kittner, Steven; Soller, Maria; Kristoffersson, Ulf; Tatlisumak, Turgut; Puschmann, Andreas; Putaala, Jukka; et al.
Abstract : Backgrounds and Purpose—: Although new methods for genetic analyses are rapidly evolving, there are currently knowledge gaps in how to detect Mendelian forms of stroke. Methods—: We performed whole-exome sequencing in 22 probands, under 56 years at their first ischemic stroke episode, from multi-incident stroke families. With the use of a comprehensive stroke-gene panel, we searched for variants in stroke-related genes. The probands' clinical stroke subtype was related to clinical characteristics previously associated with pathogenic variants in these genes. Relatives were genotyped in 7 families to evaluate stroke-gene variants of unknown significance. In 2 larger families with embolic stroke of unknown source, whole-exome sequencing was performed in additional members to examine the possibility of identifying new stroke genes. Results—: Six of 22 probands carried pathogenic or possibly pathogenic variants in genes reported to be associated with their stroke subtype. A known pathogenic variant in NOTCH3 and a possibly pathogenic variant in ACAD9 gene were identified. A novel JAK2 :c.3188G>A (p.Arg1063His) mutation was seen in a proband with embolic stroke of undetermined source and prothrombotic status. However, penetrance in the family was incomplete. COL4A2: c.3368A>G (p.Glu1123Gly) was detected in 2 probands but did not cosegregate with the disease in their families. Whole-exome sequencing in multiple members of 2 pedigrees with embolic stroke of undetermined source revealed possibly pathogenic variants in genes not previously associated with stroke, GPR142: c.148C>G (p.Leu50Val), and PTPRN2 :c.2416A>G (p.Ile806Val); LRRC1 c.808A>G (p.Ile270Val), SLC7A10 c.1294dupG (p.Val432fs), IKBKB : c.1070C>T (p.Ala357Val), and OXGR1 c.392G>A (p.Arg131His), respectively. Conclusions—: Screening with whole-exome sequencing using a comprehensive stroke-gene panel may identify rare monogenic forms of stroke, but careful evaluation of clinical characteristics and potential pathogenicity of novel variants remain important. In our study, the majority of individuals with familial aggregation of stroke lacked any identified genetic causes. Abstract : Supplemental Digital Content is available in the text.